Dampak Covid-19 bagi Pembelajaran Sekolah Serta Alternatifnya - Muthoharoh, Siti Lu’lu’il Maknun (MUNAQASYAH : Jurnal Ilmu Pendidikan dan Pembelajaran, 2020)
The impact that the COVID-19 pandemic has on the fabric of life in society is enormous. Apart from the impact on health, the economy and education have also experienced tremendous turmoil. The government has made various policies to deal with these impacts, including by means of independent isolation and the surrounding area. The government also made policies specifically for the budget budget for Covid-19. The research uses qualitative methods which focus on understanding the phenomenon of the Covid-19 Pandemic that is happening in society. The research results produce an overview of Covid-19 and the use of online media in implementing the learning system in schools.